(untitled) (Journal of Partial Differential Equations, 1994)
In this paper, we study the hypoellipticity problems for fully nonlinear panial differential equations of order m. For a solution u &#8712 C^p_loc(&#937), if the linearized operator for the nonlinear equation on u satisfies some subelliptic conditions, we can deduce u &#8712 C^&#8734(&#937) by using the paradifferential operator theory of J. -M. Bony.